(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article investigates the role and impact of Task-Based Language Teaching (TBLT) in developing the creative competence of future foreign language teachers. As the demands of 21st-century education increasingly emphasize innovation, adaptability, and learner-centered pedagogy, creativity has become a core competency for language educators. TBLT offers a pedagogical framework that fosters creativity by engaging learners in real-world, problem-solving tasks that require original thought, linguistic flexibility, and collaboration. Drawing on theoretical foundations, empirical studies, and pedagogical practices, this paper demonstrates how TBLT enhances creative competence in teacher education contexts. Practical implications for teacher training, curriculum design, and future research are discussed.